New feather mites of the genera Aniacarus and Aniibius (Acariformes: Pterolichidae) from two cuckoo species (Cuculiformes: Cuculidae) in Brazil - Mironov, Sergey V.; Hernandes, Fabio A.; Pedroso, Luiz Gustavo A. (Zootaxa, 2015)
Five new species of the family Pterolichidae are described from two common non-parasitic cuckoo species of the subfamily Crotophaginae (Cuculiformes: Cuculidae) in Brazil: Aniacarus ani sp. n. from the Smooth-billed Ani, Crotophaga ani Linnaeus, A. simplex sp. n., A. robustus sp. n., A. coronatus sp. n. and Aniibius guirae sp. n. from the Guira Cuckoo, Guira guira (Gmelin). A key to all known species of Aniacarus is provided. All four pterolichid species associated with the G. guira can occur simultaneously on one host individual. A brief review of studies of feather mites associated with Cuculidae is given.